Discrimination in hiring based on potential and realized fertility: evidence from a large-scale field experiment - Sascha Becker; Ana Fernandes; Doris Weichselbaumer (Center for Economic Studies and ifo Institute (CESifo), 2019)
Due to conventional gender norms, women are more likely to be in charge of childcare than men. From an employer's perspective, in their fertile age they are also at “risk” of pregnancy. Both factors potentially affect hiring practices of firms. We conduct a largescale correspondence test in Germany, Switzerland, and Austria, sending out approx. 9,000 job applications, varying job candidate's personal characteristics such as marital status and age of children. We find evidence that, for part-time jobs, married women with older kids, who likely finished their childbearing cycle and have more projectable childcare chores than women with very young kids, are at a significant advantage vis-à-vis other groups of women. At the same time, married, but childless applicants, who have a higher likelihood to become pregnant, are at a disadvantage compared to single, but childless applicants to part-time jobs. Such effects are not present for full-time jobs, presumably, because by applying to these in contrast to part-time jobs, women signal that they have arranged for external childcare.
Keywords: C93; J16; J71; 330; fertility; discrimination experimental economics